Os argumentos transcendentais: Kant e o problema de Hume - Lima, Túlio Sales Souza (2010)
This work whose title is "The transcendental arguments: Kant Andy Hume's problem" has as its main objective to interpret Kant's answer to Hume's problem in the light of the conjunction of the causality and induction themes which is equivalent to skeptical- naturalist reading of the latter. In this sense, this initiative complements the previous treatment seen in our dissertation, where the same issue had been discussed from a merely skeptical reading that Kant got from Hume thought and was only examined causality. Among the specific objectives, we list the following: a) critical philosophy fulfills three basic functions, a founding, one negative and one would argue that the practical use of reason, here named as defensive b) the Kantian solution of Hume's problem in the first critisism would fulfill its founding and negative functions of critique of reason; c) the Kantian treatment of the theme of induction in other criticisms would will fulfill the defense function of critique of reason; d) that the evidence of Kant's answer to Hume's problem are more consistent when will be satisfied these three functions or moments of criticism. The basic structure of the work consists of three parts: the first the genesis of Hume's problem - our intention is to reconstruct Hume's problem, analyzing it from the perspective of two definitions of cause, where the dilution of the first definition in the second match the reduction of psychological knowledge to the probability of following the called naturalization of causal relations; whereas in the second - Legality and Causality - it is stated that when considering Hume in the skeptic-naturalist option, Kant is not entitled to respond by transcendental argument AB; A⊢B from the second Analogy, evidence that is rooted in the position of contemporary thinkers, such as Strawson and Allison; in third part - Purpose and Induction - admits that Kant responds to Hume on the level of regulative reason use, although the development of this test exceeds the limits of the founding function of criticism. And this is articulated in both the Introduction and Concluding Remarks by meeting the defensive [and negative] function of criticism. In this context, based on the use of so-called transcendental arguments that project throughout the critical trilogy, we provide solution to a recurring issue that recurs at several points in our submission and concerning to the "existence and / or the necessity of empirical causal laws. In this light, our thesis is that transcendental arguments are only an apodictic solution to the Hume s skeptical-naturalist problem when is at stake a practical project in which the interest of reason is ensured, as will, in short, proved in our final considerations